Feasting on the Aam of Heaven: The Christianization of the Nisga'a, 1860-1920 - May, Nicholas
The Nisga’a of British Columbia’s rugged Pacific Coast have long forged their spirituality from both a relationship with the supernatural and other beings with whom they share the Nass Valley, and practices and beliefs brought in from abroad. In the latter half of the nineteenth century the Nisga’a began a period of intense engagement with the different Christianities that began to appear at the margins of their world. British and later Canadian missionary societies set their sights on the inhabitants of the coast while the Nisga’a themselves were exploring the newly available religious rituals and ideas they found in the emerging settler society. By 1905, the year after which ninety percent of the Indians of British Columbia were reported to be Christian, the long-serving Anglican missionary to the Nisga’a James McCullagh jubilantly declared that there was “not a heathen left” on the Nass River. This dissertation explores the process of Christianization that lay beneath such observations, focusing on how the Nisga’a understood this change in their religious life. Using missionary and government sources, as well as interviews conducted with contemporary Nisga’a, I argue that Nisga’a Christianization was a much more complex and multi-stranded endeavour than conventional framings of the subject allow. Nisga’a eagerly sought out the new Christianities on offer after mid-century, and began a long engagement with their ideas, rituals and forms. Their response is best understood as being informed by a Nisga’a cultural stance that valued new knowledge with the potential to improve their lives and respected the ability to create wealth. The religious change that occurred through their interaction with Protestant Christian forms and their promoters was marked by contingencies, the discovery and negotiation of both congruencies and differences, as well as impositions. Effects of this period of Christianization were far-reaching; the Nisga’a’s incorporation of Christianity into their religious framework significantly changed it. Influences also went both ways. As Nisga’a engaged with them, the particular forms, practices and meanings of the Christianities transplanted from Anglo-Canadian societies were tweaked and even transformed. Through this dialogical process, Christianity became a Nisga’a religion. Finally, this dissertation draws on contemporary Nisga’a memories of Christianization gleaned from interviews to examine the different ways this historical process is remembered in the Nass today, and how these understandings shape current cultural projects—including this one—that require plausible pasts. PhD